PENGARUH PENDIDIKAN KESEHATAN TENTANG MENARCHE TERHADAP KECEMASAN MENGHADAPI MENARCHE PADA SISWA KELAS 4-6 DI SDN 24 UJUNG GURUN KECAMATAN PADANG BARAT - Vino Rika Nofia (Stikes Syedza Saintika Padang, 2016)
Menarche is the first period that is common in the age range 10-16 years, in the form of periodic and cyclic bleeding from the uterus with exfoliation (desquamation) endometrium. Through interviews 4 students say anxious when asked about menstruation because they say have not ever get educational materials about menstruation causing feelings of fear and confusion when faced menarche. The purpose of this study was to determine the effect of health education on the anxiety to face menarche menarche in girls grades 4-6 at primary school N 24 Ujung Padang Kecamatan padang barat of 2015.The research design was pre-experimental approach comparasion Static-group design. The population in this study are all 4-6 grade students who have not experienced menarche were 70 people, 35 control group, 35 treatment groups using a simple method of total sampling. Data processed using univariate and bivariate frequency distribution with paired sample t-test.Results showed students who experience anxiety in the control group 29 (82.9%),16 (45.7%) in the group treated before being given health education about menarche, after being given health education students who are anxious 6 people (17, 1), the results of statistical tests found significant value 0,000.It can be concluded that there are significant health education on the anxiety to face menarche menarche in girls grades 4-6 elementary school. It is recommended to the health center staff to create educational programs to elementary school about menarche to reduce student anxiety about menarche. To the school to re-enable business activities Educational Activity (UKS).Keywords: Health Education, menarche, Anxie